ANALISIS PEMAHAMAN FUNGSI BIMBINGAN KONSELING PADA PESERTA DIDIK KELAS VII SMP NEGERI 3 PONTIANAK - Astuti, Nita Wahyu; Yuline, Yuline; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractGuidance and counseling services especially in schools and madrasas have several functions, namely: 1) understanding function, 2) prevention function, 3) alleviation function, 4) maintenance and development function, and 5) defense function. Considering the importance of the guidance and counseling function, the BK teacher has an important role in providing an understanding of the guidance and counseling functions. Therefore, BK teachers are expected to carry out their duties and provide understanding in accordance with the functions mentioned above. Therefore, researchers want to find out more about understanding the function of guidance and counseling for grade VII students of SMP Negeri 3 Pontianak. The problem in this study is how is the understanding of the guidance and counseling function in VII grade students of SMP Negeri 3 Pontianak. This study aims to obtain an overview of the understanding of the function of guidance and counseling for grade VII students of SMP Negeri 3 Pontianak. The method used is a descriptive method with a quantitative approach that is the problem solving procedure by providing an understanding of the function of guidance and counseling to grade VII students of SMP Negeri 3 Pontianak by means of statistics and explained descriptively. The sample of this study was 57 grade VII students of SMP Negeri 3 Pontianak. Data collection techniques in this study are indirect communication techniques, with data collection tools namely questionnaires. The questionnaire was previously tested for validity and reliability. The data analysis technique used is product moment analysis and continued with the coefficient of determination. Based on the results of data analysis, it shows that the understanding of the guidance and counseling function in VII grade students of SMP Negeri 3 Pontianak reaches 85.77% of these achievements in a good range.Â Keywords: Guidance and Counseling FunctionsÂ